Producción y comercialización de la papa Capiro en la región Huánuco y el vínculo con la agroindustria - Lopez y Morales, Javier (2017)
The investigation industrial ( capiro ) in her saw focuses in the study of potato’s agricultural development Región Huánuco, so much prop the internal market posteriorly in order to the exporting, grouping areas, instructing producers’s CLUSTERS, planning plantings in show to requests concerted. Industrial ( capiro ) that is a strategy, he has permitted generating a new agricultural culture in the region, a new payment culture of credits, has expedited the regional economy Sows it of the potato, sales, jobs and investments have been created to me in the country. The activity of the potato production industrial has minimized the migratory effect of the producers toward the jungle for lack of opportunity, at least in the zones where have developed me the productive programs, in the production zones of the potato industrial observes an important increment in the yearly earnings average for the sale of potatoes, of S himself. 4,681.85 in order to the year 2011 for hectare harvested, and qualitative indications  that back up this positive variation. The relation of this change in the earnings with the PRA’s and INCOPA/ADERS’s intervention comes on the side of the technical assistance and capacitating once was supplied for them they that he has had influence upon improvements in the production (quality and performance). The production performance of potato industrial (capiro) for hectare was of 15,130 kg/ha in the year 2006 to 19,810 kg/ha in order to the year 2011. These changes are not noticeable so markedly in another community that sow and another potato variety as white and yellow potato harvest.